Evidence Base Nursing Penggunaan Mobile Health Dialysis untuk Evaluasi Mandiri Adekuasi Hemodialisis pada Pasien Gagal Ginjal Kronik - Erna Dwi Kusumaningrum; Sariono Sariono (Malahayati Nursing Journal, 2023)
ABSTRACT Adequacy of hemodialysis is the fulfillment of hemodialysis doses according to the needs of the patient which is characterized by the patient feeling better, comfortable and the patient's life span is getting longer. If the dose of hemodialysis is insufficient, the patient will experience various disorders such as shortness of breath, headaches, leg cramps, nausea and vomiting, hypotension and pruritis. There is a strong relationship between adequate hemodialysis and morbidity and mortality in patients with chronic kidney failure. Objective: To determine the effectiveness of using mobile health dialysis for independent evaluation of hemodialysis adequacy in patients with chronic kidney failure This literature study uses the PRISMA approach. PICO is used to make systematic payments. The database searches used included Google Scholar, Science Direct, Cochrane, Pubmed and Wiley Online Library with the selected keywords. Results: several reviewed articles show that eHealth interventions can improve the management of sodium intake, food and fluid management. In addition, the mHealth intervention showed neutral to positive results in the management of chronic dialysis patients, and reported no significant increase in dialysis specific measures and some components of quality of life assessment. Another study shows that dietary interventions delivered via telehealth can improve the clinical and nutritional parameters of hemodialysis patients. Conclusion: The use of mobile health dialysis is effective for independent evaluation of hemodialysis adequacy in patients with chronic kidney failure. Keywords: Adequacy of Hemodialysis, Hemodialysis, Mobile Health  ABSTRAK Adekuasi hemodialisis adalah terpenuhinya dosis hemodialisis sesuai dengan kebutuhan pasien dimana ditandai dengan pasien merasa lebih baik, dan nyaman serta semakin panjang usia hidup pasien. Jika dosis hemodialisa tidak mencukupi maka pasien akan mengalami berbagai gangguan seperti sesak napas, sakit kepala, kaki kram, mual dan muntah, hipotensi dan pruritis. Ada hubungan yang kuat antara adekuasi hemodialisa dengan morbiditas dan mortalitas pada pasien gagal ginjal kronik. Mengetahui efektifitas penggunaan mobile health dialysis untuk evaluasi mandiri adekuasi hemodialisis pada pasien gagal ginjal kronik. Studi pustaka ini menggunakan pendekatan PRISMA. PICO digunakan untuk melakukan tinjauan sistematis. Database pencarian yang digunakan antara lain Google Scholar, Science Direct, Cochrane, Pubmed dan Wiley Online Library dengan kata kunci yang dipilih. beberapa artikel yang direview menunjukkan bahwa intervensi eHealth dapat meningkatkan pengelolaan asupan natrium, makanan dan pengelolaan cairan. Selain itu intervensi mHealth menunjukkan hasil netral hingga positif dalam manajemen pasien dialysis kronis, serta melaporkan tidak ada peningkatan yang signifikan dari pengukuran spesifik dialysis dan beberapa komponen penilaian kualitas hidup. Studi lain menunjukkan bahwa intervensi diet yang disampaikan melalui telehealth dapat meningkatkan parameter klinis dan gizi pasien hemodialisis. Penggunaan mobile health dialysis efektif untuk evaluasi mandiri adekuasi hemodialisis pada pasien gagal ginjal kronik. Kata Kunci: Adekuasi Hemodialisis, Hemodialisis, Mobile Health